2020
DOI: 10.12659/ajcr.926647
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hyperthermia in Treatment of Recurrent Metastatic Breast Cancer After Long-Term Chemotherapy: A Report of 2 Cases

Abstract: Case series Patients: Female, 41-year-old • Female, 42-year-old Final Diagnosis: Breast cancer Symptoms: Breast mass Medication: — Clinical Procedure: Chemotherapy • hyperthermia • radiotherapy • surgery Specialty: Oncology Objective: Unusual clinical course Background: Breast cancer has a long-term prognosis with various multimodality treatments. This report int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…[ 34 ] However, the single treatment has limited effect on the long-term prognosis due to local or distant residual lesions. [ 35 ] Our survival analysis also showed that LN metastasis decreased survival, which indicates that reduced residual tumor load plays a vital role in young patients with BC. Therefore, multimodality treatments should be encouraged, including chemotherapy, radiotherapy, and surgery, especially in young patients with TNBC.…”
Section: Discussionmentioning
confidence: 68%
“…[ 34 ] However, the single treatment has limited effect on the long-term prognosis due to local or distant residual lesions. [ 35 ] Our survival analysis also showed that LN metastasis decreased survival, which indicates that reduced residual tumor load plays a vital role in young patients with BC. Therefore, multimodality treatments should be encouraged, including chemotherapy, radiotherapy, and surgery, especially in young patients with TNBC.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, Shoji et al demonstrated that standardized RF hyperthermia could be established as a potential new treatment for rectal cancer in combination with chemoradiotherapy [ 8 ]. We have also reported the efficacy of hyperthermia combined with chemotherapy for recurrent breast cancer [ 26 ]. Our patient was also treated with 8-MHz RF hyperthermia in combination with chemotherapy, and he did not report any major adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated temperature increases the tumour sensitivity to other cancer treatments such as radiotherapy and chemotherapy, enhancing their effectiveness. Such heating can be obtained using non-ionising electromagnetic energy such as radiofrequency (RF), microwaves (MWs), or ultrasound [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%